Intoxication Due to High Dose Methotrexate in a Patient with Rheumatoid Arthritis: A Case Report - Özlem ALTINDAĞ; Birsev KÜÇÜKOĞLU (Archives of Rheumatology, 2011)
Methotrexate is an antimetabolite which impairs deoxyribonucleic acid (DNA) synthesis by competitively inhibiting folic acid metabolism. Methotrexate is successfully used in the treatment of neoplastic diseases as well as rheumatoid arthritis. Long-term use of methotrexate is quite safe and very effective in the treatment of rheumatoid arthritis. However, it may rarely cause severe side effects such as myelosupression with pancytopenia to agranulocytosis; inflammation and necrotic changes in mucosal tissues; liver cell necrosis and hepatic cirrhosis; pulmonary fibrosis and impairment in kidney functions. In this article, we report a 52- year-old female with a case of leukopenia and febrile neutropenia due to methotrexate intoxication that resulted from an accidental overdose. Although methotrexate is usually well tolerated, it may still cause unexpected and lifethreatening intoxications. Methotrexate intoxication should be considered with the presence of high fever, severe nausea, vomiting, abdominal pain, diarrhea or oral ulcers in a patient diagnosed with rheumatoid arthritis.